Sequence analysis of a mannitol dehydrogenase cDNA from plants reveals a function for the pathogenesis-related protein ELI3. - Williamson, J D (1995)
Mannitol is the most abundant sugar alcohol in nature, occurring in bacteria, fungi, lichens, and many species of vascular plants. Celery (Apium graveolens L.), a plant that forms mannitol photosynthetically, has high photosynthetic rates thought to results from intrinsic differences in the biosynthesis of hexitols vs. sugars. Celery also exhibits high salt tolerance due to the function of mannitol as an osmoprotectant. A mannitol catabolic enzyme that oxidizes mannitol to mannose (mannitol dehydrogenase, MTD) has been identified. In celery plants, MTD activity and tissue mannitol concentration are inversely related. MTD provides the initial step by which translocated mannitol is committed to central metabolism and, by regulating mannitol pool size, is important in regulating salt tolerance at the cellular level. We have now isolated, sequenced, and characterized a Mtd cDNA from celery. Analyses showed that Mtd RNA was more abundant in cells grown on mannitol and less abundant in salt-stressed cells. A protein database search revealed that the previously described ELI3 pathogenesis-related proteins from parsley and Arabidopsis are MTDs. Treatment of celery cells with salicylic acid resulted in increased MTD activity and RNA. Increased MTD activity results in an increased ability to utilize mannitol. Among other effects, this may provide an additional source of carbon and energy for response to pathogen attack. These responses of the primary enzyme controlling mannitol pool size reflect the importance of mannitol metabolism in plant responses to divergent types of environmental stress.